Vibration Analysis of Fire Pump of PEM Akamigas Cepu: A Case Study - Hernawan Novianto; Sujono (UIR PRESS, 2023)
Fire pump is a pump that is used to move water from the firewater reservoir to the location of the fire. If there is damage to this pump, the fire that occurs cannot be resolved quickly so that the impact of damage caused by fire becomes more widespread. Various problems can occur in the operation of the pump, one of which is damage to the bearings and shaft, noise occurs, decreased capacity, and even a decrease in pump efficiency. So to prevent the risk of greater damage and minimize losses in terms of cost and time, it is necessary to carry out maintenance. One of the efforts to detect damage to the pump is by vibration analysis, where from the vibration characteristics that occur, the type of damage can be determined. The purpose of this study was to determine the vibration characteristics that occur in the PEM Akamigas Cepu fire pump, by monitoring conditional vibrations using a vibration analyzer. The method is to attach the transducer to a predetermined location to determine the vibration spectrum that occurs in the axial, radial and tangential directions, then analyze the type of damage so that appropriate maintenance actions can be taken. As a result, this pump is indicated to be experiencing extreme looseness or bearing clearance problems at the pump drive end and pump non drive end as well as experiencing moderate pump imbalance, so it needs to be repaired immediately to avoid more serious damage.